Los efectos de la pandemia del COVID-19 en las áreas protegidas españolas: el caso del parque nacional Picos de Europa - Molteni, Carla Maria (Pontificia Universidad Católica del Perú. Instituto de la Naturaleza, Tierra y Energía (INTE-PUCP), 2022)
Protected areas are complex social-ecological systems; thus, they were unavoidably impacted by COVID-19. Spain is one of the most diverse countries in terms of biodiversity in the European Union and the second most visited country in 2019 and third touristic destination worldwide. Understanding the effects of the pandemic in Spanish protected areas is very important to discuss new possibilities on how to drive sustainable development on these conserved spaces and how to manage them in the event of external shocks and uncertain scenarios. Therefore, the aim of this study is to have a better understanding of the effects and opportunities of the pandemic on Spanish protected areas. To address this concern, a qualitative analysis is conducted based on an assessment of secondary literature and relevant interviews. Picos de Europa national park was chosen as case study because of its unique features. This study shows the drawbacks of the pandemic in Picos de Europa in terms of management operations, drastic fluctuation of visitors, loss of tourism revenues, vulnerability of neighboring communities, missed opportunities in conservation and education and pressure on nature. On the other hand, it poses opportunities in terms of technology, innovation, fundings, lessons learned, rise in educational and conservation activities and more awareness on the environment and rural surroundings. This study suggests that is difficult to find a win-win solution that includes the targets of nature conservation, viability of local economies and tourism activities in Picos de Europa. Ideas for management options that focus on dealing with the negative outcomes of the pandemic are suggested.

Las áreas protegidas son sistemas socioecológicos complejos y se vieron inevitablemente afectadas por la pandemia de COVID-19. España es uno de los países más diversos en biodiversidad de Europa y el tercer destino turístico mundial. Comprender los efectos de la pandemia en las áreas protegidas españolas es muy importante para discutir nuevas posibilidades sobre cómo impulsar el desarrollo sostenible en estos espacios conservados y cómo gestionarlos bajo impactos externos y escenarios inciertos. Por tanto, el objetivo de este estudio es conocer mejor los efectos y oportunidades de la pandemia en los espacios protegidos españoles. Para abordar esta preocupación, se lleva a cabo un análisis cualitativo basado en una evaluación de literatura secundaria y entrevistas oportunistas. El parque nacional de los Picos de Europa es el caso de estudio analizado debido a sus características únicas. Este estudio muestra los inconvenientes de la pandemia en Picos de Europa en términos de operación de gestión, fluctuación drástica de visitantes, pérdida de ingresos por turismo, vulnerabilidad de las comunidades vecinas, pérdida de oportunidades en conservación y educación y presión sobre la naturaleza. Por otro lado, presenta las oportunidades en términos de tecnología, innovación, ampliación de fondos, lecciones aprendidas, aumento de actividades educativas y de conservación y mayor conciencia sobre el medio ambiente y el entorno rural. Este estudio sugiere que es difícil encontrar una solución beneficiosa para todos que incluya los objetivos de conservación de la naturaleza, viabilidad de las economías locales y actividades turísticas en Picos de Europa. Se sugieren ideas para las opciones de gestión sobre cómo abordar los resultados negativos de la pandemia.
The Effects of COVID-19 Pandemic on Spanish Protected Areas: the Case of Picos de Europa National Park
Keywords: COVID-19 Pandemic; Protected Areas Management; Biodiversity; Biodiversity Conservation; Overcrowding; Social Impacts; Visitors; Spain; Picos de Europa National Park; Pandemia de COVID-19, 2020-; Gestión de áreas protegidas; Conservación de la biodiversidad; Hacinamiento; Impactos sociales; Visitantes; Parque Nacional Picos de Europa; España; https://purl.org/pe-repo/ocde/ford#2.07.01